Epidemiology of imaging-detected bone stress injuries in athletes participating in the Rio de Janeiro 2016 Summer Olympics. Issue 7 (26th October 2017) - Hayashi, Daichi; Jarraya, Mohamed; Engebretsen, Lars; D Crema, Michel; W Roemer, Frank; Skaf, Abdalla; Guermazi, Ali
Abstract : Background: Bone stress injuries are common in high-level athletics. Aim: To describe the demographics, frequency and anatomical location of stress injuries (ie, stress reaction and stress fractures) in athletes at the Rio de Janeiro 2016 Summer Olympic Games. Methods: We recorded all sports injuries at the Rio de Janeiro 2016 Summer Olympics reported by the National Olympic Committee (NOC) medical teams and in the polyclinic and medical venues. Imaging was performed through the official IOC clinic within the Olympic Village, using digital X-ray cameras and 3T and 1.5T magnetic resonance (MR) scanners. Images were read centrally and retrospectively by musculoskeletal radiologists with expertise in sports injuries. Results: 11 274 athletes (5089 women (45%), 6185 men (55%)) from 207 NOCs participated in the study. 1101 injuries were reported. Imaging revealed 9 stress fractures (36%) and 16 stress reactions (64%) in 18 female and 7 male athletes (median age 25 years, age range 18–32). Stress injuries were mostly in the lower extremities (84%), particularly tibia (44%) and metatarsals (12%), with two in the lumbar spine (8%). Stress injuries were most common in track and field athletes (44%) followed by volleyball players (16%), gymnastics (artistic) (12%) and other type of sports. Conclusions: Twenty-five bone stress injuries were reported, more commonly in women, mostly in the lower extremities and most commonly in track and field athletes. Our study demonstrates the importance of early imaging with MRI to detect stress reactions before they can progress to stress fractures.